Thesis Completion Analysis Using Optimistic Bias Possibility - Utomo, Bagus Wahyu (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Thesis is a condition that must be fulfilled by prospective graduates to be able to get a bachelor's degree. This study uses optimistic bias because in general humans experience overestimation (optimistic bias) on things that are considered as positive events, but underestimate (pessimistic biases) on negative events. This study uses the completion time of the Final Project Report as a case study. The results of this study are that there are systematic errors / biases in the accuracy data at the estimated time of completion of the final project. Accuracy time occurs Optimistic bias because the estimated value tends to be smaller when compared with the actual time value. Statistically it can be concluded that there is no difference in the accuracy of the estimated data completion of final assignments between male and female students.